ARRUAR: a produção de um site de jornalismo independente utilizando a estética do jornalismo literário - Gambarra, Rafaela Alves Nóbrega (2016)
This work proposes the production of an independent journalism website whose articles are written in the light of the Literary Journalism aesthetics, which aims to unite modalities that envisage the new, either in journalism or in the digital world – the website ARRUAR. For this purpose, studies both bibliographical and documental were conducted on the following topics: webjournalism, independent journalism and Literary Journalism. We seek to understand the new possibilities brought by the Internet in Journalism and how it affects the journalistic practice. At the same time, with the emergence of both the digital and independent journalism, we analyse the disruptor movement (CHRISTEN, 2012) attempted by these new journalistic practices. Taking into account the map of independent journalism in Brazil released by Agência Pública, we think about a business model for the website Arruar. Regarding the literary journalism, we present the characteristics of this genre (PENA, 2006; WOLF, 2005) and a brief historical background on the relationship between Journalism and Literature in Brazil and the world. In the methods, we explain the sections held on the website (investigative reporting, profiles, photojournalism and social media content curation) as well as the procedures applied (name choice, site domain, colour, typography, logo, Wordpress use, social media, funding and business model canvas). At last, we present a report about the first articles, as well as layout production, making some considerations on the trodden path and possibilities arising from this new perspective.